(untitled) (Global Journal of Science Frontier Research, 2021)
In this work we consider a nonlinear hyperbolic equations of Kirch-hoff type in viscoelasticity. By using the potential well theory we obtain the existence of a global solution. Then, we prove the intrinsic decays for the energy of the nonlinear hyperbolic equations of Kirchhoff type in viscoelasticity of relaxation kernels described by the inequality for all with H convex.